Konsep Dasar Kurikulum Multikultural (Kurikulum Sebagai Mata Pelajaran, Pengalaman, Dan Perencanaan) - Faelasup (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The research is motivated by the background that Indonesia is a country with a population of approximately 250 million people and consists of multi-ethnicity, customs, language, culture, ethnicity, religion, and different characters. From these differences, sometimes it causes violence between students, violence between teachers and students, and conflicts in the community. The research focuses are: 1) The history of curriculum development in Indonesia, 2) The basic concept of a multicultural curriculum. The research method is a type of library research with literature studies, articles, scientific journals, and searches for literature related to the curriculum. The history of curriculum development is divided into three periods, namely 1). The Old Order Period (1945-1965), in which there is 1947 Lesson Plan curriculum, 1952 Curriculum Lesson Plan, 1952 Curriculum, 1964 Curriculum Education Plan 1964, 2). The New Order period, in which there was the 1968 curriculum, the 1975 curriculum, the 1984 1975 curriculum that was perfected, and the 1994 curriculum, 3) the Revormation Period (1999-present), consisting of a competency-based curriculum (KBK). Education unit level curriculum (KTSP), and Curriculum 2013. The basic concept of multicultural curriculum: 1) curriculum as a subject, includes a), content integration in instructional. b), the knowledge construction process in instructional. c), An equity pedagogy instructional. d). Training participation in instructional. e) Prejudice reduction in instructional. 2) curriculum as experience, namely reading playing an instrument, socializing, having a positive attitude, and so on, so that students can understand and understand differences, 3) curriculum as planning, that is, the curriculum is seen as a plan drawn up to smooth the teaching and learning process under guidance and responsibility of schools or educational institutions and teaching staff.